Zu semantischen Aspekten der Wortkombinatorik - Bielińska, Monika (Glottodidactica, 2000)
The process of language production is the correct connecting of separate words to bigger meaningful units and eventually the forming of sentences is based on certain rules called combination or compatibility rules. This article focuses on the semantic part of the combination mechanism, because it seems to be the primary one. The syntactic part will be discussed only briefly in the introductory chapter. The investigation encompasses the following aspects: a presentation of mechanisms of syntagmatic lexem connecting, restrictions of selection within word combinations and finally the separation of semantic selection rules from restrictions that are based only on language usage. Such investigations can be very useful for the description of contextual word behavior and consequently for foreign language teaching, especially when these investigations and their results are compared with those in other languages. Breaking the combination rules caused by interference may lead to many semantic-lexical mistakes.